Effects of pruning on canopy microenvironment, branch composition and nut quality in Xinjiang walnut - HAN Liqun; ZHAO Yu; ZHAO Guoqing; ZHANG Hui; MA Kai (Guoshu xuebao)
[Objective] Pruning is a crucial aspect in fruit cultivation management. The suitable pruning can enhance ventilation and light penetration within the canopy, improve photosynthetic capacity and light energy utilization efficiency, thereby establishing a better balance between vegetative and reproductive growth, and ultimately increasing the fruit quality. For the tall arboreal trees like walnut, adopting efficient and simple pruning method can significantly reduce production costs and enhance economic benefits. The aim of this study was to examine the effects of different pruning models on canopy microenvironment, branch composition and nut quality in walnut, and investigate the suitable and efficient pruning model for Xinjiang walnut trees. [Methods] The 15-year-old Xinfeng trees, primary walnut cultivar in Xinjiang, were taken as the experimental materials. Three models including mechanical pruning, mechanical and manual-assisted pruning, and manual pruning were adopted, with unpruned trees as the control. Parameters such as canopy temperature, relative humidity, light intensity, photosynthetic capacity, photosynthetically active radiation and chlorophyll content (SPAD) were measured. The number of mixed buds, fruit settings, newly developed bearing branches and mixed buds were quantified. The contents of endogenous hormones in the mixed buds were determined by the enzyme-linked immunosorbent assay (ELISA). The plant yield, nut count, nut weight, and rates of empty and shriveled nuts were recorded during the fruit harvest period. Additionally, the kernel quality parameters including crude fat, crude protein and soluble sugar contents were tested. The parameter indicators were analyzed through clustering and correlation methods. The quantitatively comprehensive method was adopted to evaluate the different pruning models based on the AHP-CRITIC combination weight methods and the TOPSIS model. [Results] After pruning, the height and crown width of walnut trees were reduced, and ventilation and light penetration were improved. The relative humidity of canopy decreased, while light intensity, photosynthetic capacity, and the SPAD values of leaves increased, and the net photosynthetic rate and photosynthetically active radiation were significantly enhanced, which collectively enhanced the microenvironment. Photosynthesis is the foundation of walnut growth. Through pruning, light could be utilized more efficiently, which influenced the growth and development of leaves and branches, and ultimately shaped the formation of fruit quality. The results showed the net photosynthetic rate within the canopy exhibited an increasing gradient from the inner canopy to the outer, the mechanical and manual-assisted pruning was higher across all canopy zones compared to other pruning methods. The annual bearing branches and flower buds are critical for the formation of yield and quality. Pruning optimized light utilization and influenced the growth of annual bearing branches. The total number of mixed buds and female flowers in the selected annual bearing branches did not differ significantly among the pruning models. However, the number of fruit set, and newly formed bearing branches and mixed buds increased significantly. Specifically, the mechanical and manual-assisted pruning produced the highest number of new annual branches, and the manual pruning generated the most mixed buds. Additionally, the pruning promoted the accumulations of growth-promoting hormones, such as GA3 and IAA, with the highest levels observed in mixed buds under the mechanical and manual-assisted pruning and manual pruning, respectively. Conversely, the growth-inhibiting hormone ABA decreased, and showed significant reductions in apical buds under manual pruning condition and lateral buds under mechanical and manual-assisted pruning conditions. Yield and nut quality are the most critical indicators for evaluating the rationality of pruning models in the fruit tree. The pruning can also establish physiological balance between vegetative growth and reproductive capacity, helping to maintain tree structure and improve nut quality. This study revealed that while pruning reduced the yield per plant, it significantly increased the nut weight and reduced the rates of empty and shriveled nuts with the lowest 4.3% in mechanical and manual-assisted pruning. Furthermore, pruning enhanced kernel quality, with significant increase in crude fat, crude protein, and soluble sugar contents from 17.9% to 42.7%. Among the three pruning models, the mechanical and manual-assisted pruning led to substantial improvements in nut quality, and the yield per plant could recover rapidly. Cluster analysis of the measured parameters revealed distinct groupings based on the different pruning methods. Negative indicators such as ABA, yield per plant, nut numbers and the rates of empty and shriveled nuts were clustered, while other parameters formed another. Correlation analysis further indicated that microenvironmental indicators were positively correlated with the numbers of annual fruiting branches, mixed buds, and nut quality traits. Pruning reduced the number of branches, leading to a temporary decline in yield per plant. However, yield could quickly recover through the changes of canopy microenvironment conditions. Based on the comprehensive evaluation, mechanical and manual-assisted pruning emerged as the optimal pruning model. [Conclusion] Pruning significantly enhanced the canopy microenvironment, facilitated the reconstruction of annual bearing branches, and improved the nut quality of walnut. The integration of pruning machinery with simplified manual agronomic practices for mature walnut trees in Xinjiang represents an economically viable and highly efficient pruning model.